Peningkatan Kemampuan Pemecahan Masalah Matematis Melalui Model Pembelajaran Berbasis Masalah Dengan Pendekatan Tarl Pada Peserta Didik Kelas X PM 3 SMK Negeri 2 Semarang - Ida Nurjannah; Suprihatin; Lilik Ariyanto (Jurnal Pendidikan Guru Profesional, 2024)
This study aims to improve the mathematical problem-solving ability of grade X PM 3 students at SMK Negeri 2 Semarang through the application of a problem-based learning (PBL) model with the Teach at the Right Level (TaRL) approach. This classroom action research was conducted in 2 cycles. The results of the study showed an increase in the mathematical problem-solving ability of students from Cycle 1 to Cycle 2. In Cycle 1, the average score for the mathematical problem-solving ability test was 80.89 with an 88.6% completion rate. After making improvements in Cycle 2, the average score increased to 93 with a 100% completion rate. Based on the observation results, students were seen to be more enthusiastic and actively involved in the learning process. They were able to understand problems, plan solution strategies, carry out plans, and recheck answers with teacher guidance according to the ability level of each group. It can be concluded that the application of a problem-based learning (PBL) model with the Teach at the Right Level (TaRL) approach is proven to be effective in improving the mathematical problem-solving ability of grade X PM 3 students at SMK Negeri 2 Semarang